Peran Tokoh Masyarakat Dalam Pembagian Harta Waris terhadap Anak Angkat - Nabilah Falah (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Adopted children cannot inherit the assets of their adoptive parents and only have rights through a mandatory testament, the amount of which cannot be more than 1/3 of the assets left by their adoptive parents as stated in Article 209 paragraph (2) KHI. The fact that happened in the Bobosan sub-district there were 3 (three) cases of inheritance distribution for adopted children who received the entire adoptive parent's inheritance. This paper attempts to explain the role of community leaders in the distribution of the inheritance of adopted children that occurred in the Bobosan sub-district, Banyumas Regency. This type of research is field research using an empirical juridical approach. The data source used was obtained from primary data sources in the field by conducting in-depth interviews with the informants studied. The method used in the qualitative analysis, namely describing, interpreting and interpreting research data by linking role theory (role theory). Based on the results of the study it can be concluded that the role of community leaders in the distribution of the inheritance of adopted children in the Bobosan sub-district is a religious figure who is trusted by the community to be able to make decisions on inheritance distribution by considering the value of more benefit. According to the religious leader, the division of inheritance that occurs is a need for Ḍaruriyat, adopted children who live in dependence to live in their parents' house and continue the business of their adoptive parents. So that the family and the surrounding community consider the adopted child to be the full successor of the assets and efforts of the adoptive parents in order to prioritize the benefit of the adopted child. Keywords: Roles, Religious Leaders, Inheritance, Adopted Children